Lack of interaction between lysine levels fed in growing and finishing diets - Steve, Rops; Marty, Heintz; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 1,200 pigs were used to determine whether dietary lysine level fed in the growing phase influenced the response to lysine level fed in the finishing phase. Pigs were fed either an adequate or low lysine level during the growing (60 to 170 lb) and/ or finishing phase (170 to 265 lb). Feeding a deficient lysine level decreased ADG and F/G during the phase when the deficient diet was fed; however, lysine level fed in the growing phase did not influence the response in the finishing phase. Carcass parameters were influenced more by the lysine level fed in the finishing diets.
Keywords: Swine; Lysine; Growing-finishing pigs; Compensatory gain; Growth